Incidence of Predators and Anthropogenic Activities Affecting Beekeeping in Nigeria - A. A., Lawal; S., Mustapha; A. A., Oyerinde (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2021)
This study evaluated the incidence of predators and anthropogenic activities affecting beekeeping in Nigeria. Questionnaires were administered in Oyo, Ogun and Osun States in the Forest Vegetation and Kaduna, Niger and Kano States in the Savanah vegetation zones of Nigeria. Data obtained were analyzed with parametric statistical tool of mean. The result showed that the largest populations of beekeepers were Bachelor Degree and National Certificate in Education NCE holders (25.0% each), MSc (8%), National Diploma ND (8%) and Postgraduate Diploma PGD (9%).  Assessment of human activities that were harmful to beekeeping identified by respondents in the forest vegetation zones revealed indiscriminate use of pesticide (16.67%), theft (33.33%) and herdsmen activity (cattle rearing) (31.82%) while savannah vegetation zones had the following record, indiscriminate use of pesticide (25.00%), theft (35.33%) and herdsmen activity (35.71%). Avoidance of scattering honeybee (Apis mellifera L.) combs around the apiary was found as the most effective method in preventing spread of insect pests. Other methods include: hive sanitation, hive positioning, handpicking of insects, the use of spent engine oil, regular weeding, fencing of apiary and use of bee pen. The hives painted with green coloured paint was reported by respondent to control wasp, spider, termites and lesser wax moth. Beekeepers reported weeding as the most effective method used in controlling predators as it was noted that apiaries regularly weeded controlled the following predators with their respective incidence level: rat (8.33%), snake (12.50%), toad (29.7%), frog (20.83%) and ghecko (37.50%) while the most significant was lizard incidence which was 54.17%. Report from respondents on traditional methods to detect apiary problems categorized into predator and human activities include: decreasing size of colony, majority of bees staying outside the hive, sighting of pests in the apiary and abscondment of bees while human interference was noticed with dead bees found in and outside the hive, inactive bees, trace of burnt grasses and shrubs in the apiary and felled hives from stands.